2021
DOI: 10.1016/j.sjbs.2020.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, sarcopenia and health related outcomes among elderly patients in Saudi Arabia

Abstract: Objective To determine the prevalence of frailty and sarcopenia among elderly patients in Saudi Arabia and explore if there are significant association between frailty and sarcopenia. Methods A total of 498 patients from public tertiary hospital in Saudi Arabia participated in this descriptive cross-sectional study between March 2019 to June 2019. All participants answered a 5-part questionnaire, which includes demographic data, Edmonton Frail Scale, SARC-F and question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The quality of all of the included studies ranged from 3 to 8 as per the Newcastle-Ottawa scale with a mean score of 6.18 for all included studies indicating satisfactory quality. One study scored 3 [ 17 ] two studies scored 5 [ 16 , 27 ] two studies scored 6 [ 23 , 24 ] five studies scored 7 [ 15 , 19 , 25 , 26 ] and one study scored 8 [ 20 ] No studies scored 1, 2, 4 or 9. Table 2 shows the quality rating for all included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of all of the included studies ranged from 3 to 8 as per the Newcastle-Ottawa scale with a mean score of 6.18 for all included studies indicating satisfactory quality. One study scored 3 [ 17 ] two studies scored 5 [ 16 , 27 ] two studies scored 6 [ 23 , 24 ] five studies scored 7 [ 15 , 19 , 25 , 26 ] and one study scored 8 [ 20 ] No studies scored 1, 2, 4 or 9. Table 2 shows the quality rating for all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in Europe, the United States, Canada, and Australia have shown that frailty rates ranged between 4 and 60% [ 14 ]. The available data from the Middle East countries revealed an overall prevalence of frailty among individuals who are 60 years old or more of 47% in the United Arab Emirates [ 15 ], 40% in Saudi Arabia [ 16 ], 66.3% in Egypt [ 17 ], 60% in Iran [ 18 ], 28.7% in Turkey [ 19 ], and 81.3% in Lebanon [ 20 ]. However, these discrepancies in the prevalence of frailty require a comprehensive overview of frailty prevalence in these countries since there are commonly shared geographical and demographical factors.…”
Section: Introductionmentioning
confidence: 99%
“…Another study witnessed the association of frailty with sarcopenic elderly patients [ 49 ]. This descriptive cross-sectional study involves the participation of 498 patients from a public tertiary hospital.…”
Section: Research On Frailty In Ksa Until Present Daymentioning
confidence: 99%
“…The prevalence was higher in nursing-home individuals, reaching 51% in men and 31% in women and in hospitalized individuals it was 23% in men and 24% in women. [ 13 ] In Saudi Arabia, few studies have been conducted to assess the prevalence of sarcopenia among Saudis; however, they were based on subjective assessment[ 14 15 ] or on the Asian Working Group for Sarcopenia (AWGS) criteria (not based on reference values for Saudis). [ 16 ]…”
Section: Introductionmentioning
confidence: 99%